Idiopathic pericarditis - an autoinflammatory disease? - Blank, Norbert; Lorenz, Hanns-Martin (Current rheumatology reports, 2019)
Purpose of the ReviewIdiopathic acute and recurrent pericarditis are rare diseases of unknown origin. Here, we review trigger factors, pathomechanism, and treatment options for acute and recurrent pericarditis.Recent FindingsAcute pericarditis can be triggered by viral infections, myocardial ischemia, heart catheter interventions, cardiac surgery or seem to occur without any trigger. Earlier reports about viral nucleic acids in the effusion or myocardial autoantibodies in serum were detected only in a minority of patients. The current pathomechanistic concept focuses on the innate immune system. Clinical trials revealed that colchicine and anti-IL1β-targeted medication were effective to control acute and recurrent attacks.SummaryActivation of the innate immune system in pericarditis suggests that autoinflammation contributes to acute and recurrent pericarditis. The efficacy of colchicine and anti-IL1β-targeted medication in clinical trials indicates that acute and recurrent pericarditis should be regarded as an autoinflammatory disease. Therefore, idiopathic pericarditis should be considered as an autoinflammatory disease.